Study on application of cement substituting mineral fillers in asphalt mixture - Jie Wang; Meng Guo; Yiqiu Tan (International Journal of Transportation Science and Technology, 2018)
In order to investigate the potential of cement fillers applying in asphalt pavement instead of mineral fillers, this research did a comprehensive study, including the raw materials properties tests, mix design, and verification of mixture performance. Results show that in terms of the physical and volumetric properties, the cement fillers are similar with mineral fillers. The mix design process of asphalt mixture containing cement fillers can refer to the common asphalt mixture. The optimum asphalt/aggregate ratio was 5.0% for the materials and gradation selected in this research. The residual stability of immersion Marshall stability test was 78.9%, and the TSR of freeze–thaw splitting test was 74.4%. Both of them meet the specification requirements. The dynamic stability was 1169 time/mm, the seepage coefficient was 63.4 ml/min. These larger data than the required values demonstrated the good functional performance of asphalt mixture containing cement fillers, including the rutting resistance and the anti-permeable ability. Keywords: Asphalt mixture, Cement filler, Volumetric property, Mechanical property, Functional performance